Price regulation, inflation, and nominal rigidity in housing rents - Conor O'Toole; Maria Martinez-Cillero; Achim Ahrens (The Economic and Social Research Institute (ESRI), 2019)
In this paper, we explore the impact of a housing rent inflation cap of 4 per cent on price changes for tenancy contracts. We assess the implications of the regulations on the share of the market experiencing: 1) a price decline; 2) unchanged rents (nominal rigidity); 3) a positive growth rate below the cap; 4) the maximum allowable growth; and 5) growth above the cap. Our identification strategy uses a multinomial logit difference-in-difference approach applied to a novel micro panel dataset at the property level in Ireland. We find the overall inflation rate fell by 3 percentage points following the regulations, driven by a reduction in the share of individual contracts pricing above the regulatory maximum. We find an increase in the likelihood of nominal rigidity at the expense of high-growth rates. However, we also find a higher probability of small increases, at or below the regulatory level, relative to nominal rigidity after the regulations which is consistent with landlords trying to maintain real returns as price resets are not allowed between tenancies. Heterogeneous effects by landlord type and starting rent levels are evident.
Keywords: R21; R28; R31; 330; Rent control; nominal rigidity; price stickiness; Ireland